Operative morbidity and mortality for colorectal cancer: 10-years’ experience - Ahmad, H. Viqar; Khan, Zubair Afzal (International Surgery Journal, 2019)
Background: Operative outcomes for patients with colorectal cancer are heavily dependent on the quality of surgery, the quality of pre-operative staging and treatment selection. The objective of this study was to study the operative morbidity and mortality in patients with colorectal cancer. Methods: The records of patients, with histologically proven colon or rectal cancer and underwent operative procedure, have been prospectively documented. A detailed analysis was made of patients who had a hospital stay of more than 15 days and who died within 30 days of surgical procedure. Results: 311 patients of colorectal cancer were operated. 19 patients died within 30 days of operation, an overall OMR of 6.10%. 50.80% of patients had operative morbidity events. OMR and morbidity was higher in patients undergoing emergency surgical procedure, in elderly patients, in females, patients with poor pre-operative ASA grading and in patients with advanced stages tumour. Conclusions: Adoption of various modalities of have to be considered in perspective of the age of the patient, pre-operative performance status, the type, nature and urgency of operation and pathological stage of the disease which have a bearing on the operative morbidity and mortality.